Pengembangan UMKM Sektor Pangan melalui Peningkatan Kualitas, Keamanan, dan Inovasi Produk - Putri Yufrida Giarti Saparingga; Arif Yahya (Jurnal Pusat Inovasi Masyarakat (PIM), 2019)
Development of MSME in the food sector faces various problems, especially in the quality and safety of product. The other problem is low of value added agricultural commodities as an innovative processed food product that can be developed at the MSME scale. These problems need to be overcome through the formulation of appropriate solutions. The purpose of ASEAN Service Learning Program in Mendak Village, Dagangan, Madiun is to conduct training and assistance the MSME to solving the probems.The MSMEs that involved in this activity are Dodol Loren MSMEs and Gula Aren MSME. The method of implementing the activity begins with a field observation to identify the problem, a discussion about the problem and finding solution, and strategy to solve the problem. The programs are socialization of Good Manufacturing Practice (GMP) and training to make Cici Banana Dodol. Sialization of secondary packaging of palm sugar as a solution to the problem of Gula Aren MSME, and training on making tortilla with the seasoning powder as a solution to the problem of low value added of local agricultural commodities. As a result of the programs the owner of MSMEs in the Mendak Village were able to implement good manufacturing practices so as to improve the quality and safety of the product. Besides that, the villagers were able to process the local comodities as an innovation of processed food products such as Tortillava and Cici Banana Dodol on an MSME scale.